Rational Overconfidence and Social Security - Carsten Krabbe Nielsen (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
Is an assumption of bounded rationality needed to explain Social Security and other mandatory pension plans? In this contribution we argue that when rational agents hold inconsistent expectations such programs may be justified. Two of the features that distinguish Social Security and many other state mandated pension plans around the world are that (i) a minimum level of savings for retirement is imposed on most citizens and (ii) individuals cannot freely decide how their contributions are invested. Here, a rationale for these two features, based on rational overconfidence, is proposed. Rational overconfidence is present when equally informed agents hold diverse confident, rational beliefs. The fact that beliefs are diverse means that all of them cannot be correct, hence seen as a collective agents do not act optimally. In the face of rational overconfidence, Pareto efficiency is no longer the natural criterion for comparing policies and we suggest ex-post welfare optimality in stead. This criterion makes amends for the possible inconsistencies of agents' beliefs. Our results on social security are based on a methodology that places itself strictly between the traditional neoclassical approach and that championed by behavioral economics. This methodology does not deviate from the neoclassical assumption of rationality but only broadens it and can therefore readily be applied to many public policy issues.
Keywords: D01; D02; D63; D81; D84; H55; 330; Subjective Expectations; Rational Beliefs; Ex-post Welfare Optimality; Social Security; Rational Overconfidence; Portfolio Choice